Disentangling the Meaning and Verb Collocates of Terms through Unabridged Statutory Context with implications for teaching: Employer, Hirer and Temporary Work Agency in UK Employment Legislation - Rzepkowska, Agnieszka (2024)
The paper addresses the issue of pinpointing the meaning of legal collocations of the terms: employer, hirer and temporary work agency, and through them the meaning of the legal terms in real legislative documents. This genre-specific corpus study sheds some light on how real legal acts can be used in the course of legal language learning to familiarise students with verbal collocations specific to employment law. The findings suggest that verb collocates disclose the system-bound meaning of terms and mirror the place of terms in the terminological system. Comparing legal definitions with information revealed through a purposeful analysis of verbal collocations in statutory contexts proves that the latter may show additional information about the concepts represented by terms. Although unabridged legal texts can be an insufficient source of specialist collocations for specialist language learners, if appropriately easified (Bhatia 1983), they may become a valuable learning material.
Keywords: verbal collocation; corpus; employment law; legal genre; legal language teaching; LSP; multiword item